How Do Debit Cards Affect Cash Demand? Survey Data Evidence - Helmut Stix (Oesterreichische Nationalbank (OeNB), 2003)
This paper analyzes how EFT-POS payments and ATM withdrawals affect purse cash demand. In particular, survey data about Austrian individuals are employed to estimate a cash demand equation which takes account of sample selection effects. The results reveal that purse cash demand is significantly affected by debit card usage and that there are significant differences in cash demand for individuals with different debit card usage frequencies. For example, the point estimates imply that individuals who pay frequently with their debit card hold about 20% less purse cash than all others while frequent ATM withdrawals are associated with about 18% less purse cash demand. Due to the relative small share of frequent users, currently, aggregate purse cash demand is not very strongly affected by EFT-POS payments. However, if usage behavior shifts towards higher usage frequencies, then the findings of this study suggest that purse cash demand will decrease substantially.
Keywords: E41; E58; D12; 330; Cash Demand; Payment Cards; Cash Substitution